The world of norm may produce gas - Meres, Jonathan (London : Orchard, 2012)
Norm knew it was going to be one of those days when he got blamed for global warming. And that's just the tip of the iceberg... It seems like the whole world has gone mad. His dad's obsessed with gas, his best friend has come down with a case of hormones and his brother is in dire need of deodorant. Looks like there's going to be quite a stink. Is life still unfair for Norm ABSO-FLIPPING-LUTELY! Jonathan Meres follows up May Contain Nuts and May Cause Irritation with another laugh-out-loud story about Norm, a boy who can't understand why everything always seems unfair...
H
b
b